Creative productivity of elderly scientists - V. M. Postavnev; I. V. Postavneva; V. P. Peskov; A. M. Dvoinin (Acta Biomedica Scientifica)
The article presents the results of studying the personality characteristics of elderly scientists who have maintained scientific productivity for a long time. The problem that has to be solved and has got a huge scientific and practical significance is to find the psychological preconditions for the peak achievements of scientists and to define the social and psychological factors that contribute to maintaining the high productivity of elderly scientists for a long time.The aim of the study is to determine the key personality traits of famous elderly scientists at the stages of their professional development.Research methods. The presented data were obtained using the research interview “Life Values and Life Path”, developed by V.S.  Mukhina. Empirical material was collected in the course of interviewing famous Russian scientists of older age (from 65 to 94 years old), involved in research activities and making a significant contribution to the development of the humanities and technical sciences. When forming the sample, we followed the logic of V.S. Mukhina, who interviewed older scientists who are the founders and leaders of well-known scientific schools, who have a doctorate in science, the academic title of professor, membership in the academy of the Russian Academy of Sciences, Russian Academy of Medical Sciences or Russian Academy of Education and continue active scientific work. Data on the peak achievements of older scientists were taken from the scientometric databases of the Russian Science Citation Index and the Russian State Library.Results. The data representing the peak achievements of the elderly scientists were taken from the scientometric databases and interpreted according to the provisions of differential and acmeological analysis for professional activities of scientists. The analysis of interviews, autobiographical descriptions and peak achievements of the elderly scientists allowed to reveal that the peak achievement (acme) is the joint result of psychological preconditions (personal traits of scientists, physical conditions) and social conditions of professional activity (social status of a scientist, belonging to a scientific school, availability of organizational and financial resources). The several productive periods, which are called within the acmeology field as “micro-acme”, can be indicated in the scientific work of elderly scientists throughout the period of their scientific activity. At the same time, the peak achievements of scientists as a rule are spaced in time with an optimal combination of preconditions and conditions for scientific creativity.